1996
DOI: 10.1109/43.552089
|View full text |Cite
|
Sign up to set email alerts
|

Charge-based fault simulation for CMOS network breaks

Abstract: We de ne a network break as a break fault in the p-network or in the n-network of a CMOS cell that breaks one or more transistor paths between the cell output and Vdd or GND. Previous work, mostly in the context of transistor stuck-open faults, studied test invalidation due to transient paths to Vdd or GND, and due to charge sharing. In this paper we show the importance of Miller feedthrough and feedback capacitances in network break test invalidation, which was ignored by previous work. We present a new fault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We need the capability to detect these faults. Earlier, it was shown that such faults may be detected by inducing transition in the adjacent nets and thereby injecting charge into the floating nets [18].…”
Section: Fault Testabilitymentioning
confidence: 99%
“…We need the capability to detect these faults. Earlier, it was shown that such faults may be detected by inducing transition in the adjacent nets and thereby injecting charge into the floating nets [18].…”
Section: Fault Testabilitymentioning
confidence: 99%
“…In such case, the analogue voltage can be pre-computed and saved in the corresponding cell test view. The proposed model, due to the lower LOP fault incidence in CMOS circuits [19][20][21], deliberately does not take into account charge sharing effects and transient paths to V DD or V SS effects [22].…”
Section: Lop Faults Modelsmentioning
confidence: 99%
“…One common defect mechanism that can cause large delay effects is floating nodes resulting from CMOS open defects. Small leakage currents in the defective devices, or in nominally turned off parallel paths, can sometimes slowly charge the node to the correct logic level [1], resulting in delay fault behavior from the opens. Figure 1 illustrates this for a simple NAND gate.…”
Section: Introductionmentioning
confidence: 99%